Question
upstudy study bank question image url

TOPIC: Algebra Sub-topic: Solve Quadratic equations by factorisation Solve for \( x \) : One a) \( 3 x^{2}-6 x=0 \) b) \( x^{2}-81=0 \) c) \( x^{2}-x=12 \) d) \( x(x-9)=-14 \) e) \( 3 x^{\frac{2}{3}}-7 x^{\frac{1}{3}}+2=0 \) f) \( x-3 x^{\frac{1}{2}}-4=0 \)

Ask by Johnston Carter. in South Africa
Feb 02,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Solutions:** - **a)** \( x = 0 \) and \( x = 2 \) - **b)** \( x = 9 \) and \( x = -9 \) - **c)** \( x = 4 \) and \( x = -3 \) - **d)** \( x = 7 \) and \( x = 2 \) - **e)** \( x = \frac{1}{27} \) and \( x = 8 \) - **f)** \( x = 16 \)

Solution

Sure! Let's solve each of the quadratic equations by factorization step by step. --- ### **a) \( 3x^{2} - 6x = 0 \)** **Step 1: Factor out the greatest common factor (GCF).** The GCF of \( 3x^{2} \) and \( -6x \) is \( 3x \). \[ 3x^{2} - 6x = 3x(x - 2) = 0 \] **Step 2: Apply the Zero Product Property.** If \( AB = 0 \), then either \( A = 0 \) or \( B = 0 \). \[ 3x = 0 \quad \text{or} \quad x - 2 = 0 \] **Step 3: Solve for \( x \).** \[ x = 0 \quad \text{or} \quad x = 2 \] **Solution:** \( x = 0 \) and \( x = 2 \) --- ### **b) \( x^{2} - 81 = 0 \)** **Step 1: Recognize the difference of squares.** \[ x^{2} - 81 = x^{2} - 9^{2} = (x - 9)(x + 9) = 0 \] **Step 2: Apply the Zero Product Property.** \[ x - 9 = 0 \quad \text{or} \quad x + 9 = 0 \] **Step 3: Solve for \( x \).** \[ x = 9 \quad \text{or} \quad x = -9 \] **Solution:** \( x = 9 \) and \( x = -9 \) --- ### **c) \( x^{2} - x = 12 \)** **Step 1: Bring all terms to one side to set the equation to zero.** \[ x^{2} - x - 12 = 0 \] **Step 2: Factor the quadratic equation.** We need two numbers that multiply to \(-12\) and add to \(-1\). \[ (x - 4)(x + 3) = 0 \] **Step 3: Apply the Zero Product Property.** \[ x - 4 = 0 \quad \text{or} \quad x + 3 = 0 \] **Step 4: Solve for \( x \).** \[ x = 4 \quad \text{or} \quad x = -3 \] **Solution:** \( x = 4 \) and \( x = -3 \) --- ### **d) \( x(x - 9) = -14 \)** **Step 1: Expand and bring all terms to one side.** \[ x^{2} - 9x + 14 = 0 \] **Step 2: Factor the quadratic equation.** We need two numbers that multiply to \(+14\) and add to \(-9\). \[ (x - 7)(x - 2) = 0 \] **Step 3: Apply the Zero Product Property.** \[ x - 7 = 0 \quad \text{or} \quad x - 2 = 0 \] **Step 4: Solve for \( x \).** \[ x = 7 \quad \text{or} \quad x = 2 \] **Solution:** \( x = 7 \) and \( x = 2 \) --- ### **e) \( 3x^{\frac{2}{3}} - 7x^{\frac{1}{3}} + 2 = 0 \)** **Step 1: Make a substitution to simplify the equation.** Let \( y = x^{\frac{1}{3}} \). Then \( y^{2} = x^{\frac{2}{3}} \). Substitute into the equation: \[ 3y^{2} - 7y + 2 = 0 \] **Step 2: Factor the quadratic in \( y \).** We need two numbers that multiply to \(3 \times 2 = 6\) and add to \(-7\). \[ 3y^{2} - 6y - y + 2 = 0 \\ 3y(y - 2) -1(y - 2) = (3y - 1)(y - 2) = 0 \] **Step 3: Apply the Zero Product Property.** \[ 3y - 1 = 0 \quad \text{or} \quad y - 2 = 0 \] **Step 4: Solve for \( y \).** \[ y = \frac{1}{3} \quad \text{or} \quad y = 2 \] **Step 5: Substitute back \( y = x^{\frac{1}{3}} \) and solve for \( x \).** - For \( y = \frac{1}{3} \): \[ x^{\frac{1}{3}} = \frac{1}{3} \\ x = \left( \frac{1}{3} \right)^{3} = \frac{1}{27} \] - For \( y = 2 \): \[ x^{\frac{1}{3}} = 2 \\ x = 2^{3} = 8 \] **Solution:** \( x = \frac{1}{27} \) and \( x = 8 \) --- ### **f) \( x - 3x^{\frac{1}{2}} - 4 = 0 \)** **Step 1: Make a substitution to simplify the equation.** Let \( y = x^{\frac{1}{2}} \) (which means \( y = \sqrt{x} \)). Then \( y^{2} = x \). Substitute into the equation: \[ y^{2} - 3y - 4 = 0 \] **Step 2: Factor the quadratic in \( y \).** We need two numbers that multiply to \(-4\) and add to \(-3\). \[ (y - 4)(y + 1) = 0 \] **Step 3: Apply the Zero Product Property.** \[ y - 4 = 0 \quad \text{or} \quad y + 1 = 0 \] **Step 4: Solve for \( y \).** \[ y = 4 \quad \text{or} \quad y = -1 \] **Step 5: Substitute back \( y = \sqrt{x} \) and solve for \( x \).** - For \( y = 4 \): \[ \sqrt{x} = 4 \\ x = 16 \] - For \( y = -1 \): \[ \sqrt{x} = -1 \] Since \( \sqrt{x} \) represents the principal (non-negative) square root, \( \sqrt{x} = -1 \) has no real solution. **Solution:** \( x = 16 \) --- **Summary of Solutions:** - **a)** \( x = 0 \) and \( x = 2 \) - **b)** \( x = 9 \) and \( x = -9 \) - **c)** \( x = 4 \) and \( x = -3 \) - **d)** \( x = 7 \) and \( x = 2 \) - **e)** \( x = \frac{1}{27} \) and \( x = 8 \) - **f)** \( x = 16 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve these quadratic equations by factorization, we'll start by rewriting each equation in standard form (if necessary) and then factor them to find the roots. Here’s the solution for each equation: a) \( 3x^{2} - 6x = 0 \) Factor out \( 3x \): \( 3x(x - 2) = 0 \) So, \( x = 0 \) or \( x = 2 \). b) \( x^{2} - 81 = 0 \) This is a difference of squares: \( (x - 9)(x + 9) = 0 \) So, \( x = 9 \) or \( x = -9 \). c) \( x^{2} - x - 12 = 0 \) Factor the quadratic: \( (x - 4)(x + 3) = 0 \) So, \( x = 4 \) or \( x = -3 \). d) \( x(x - 9) = -14 \) → move -14 to the left side to form a standard quadratic: \( x^2 - 9x + 14 = 0 \) Factoring gives: \( (x - 7)(x - 2) = 0 \) So, \( x = 7 \) or \( x = 2 \). e) Let \( y = x^{\frac{1}{3}} \): Then the equation becomes \( 3y^{2}-7y+2=0 \). Factoring gives: \( (3y - 1)(y - 2) = 0 \) So, \( y = \frac{1}{3} \) or \( y = 2 \), which implies \( x = \left(\frac{1}{3}\right)^{3} \) or \( x = 2^{3} \), leading to \( x = \frac{1}{27} \) or \( x = 8 \). f) \( x - 3\sqrt{x} - 4 = 0 \) → let \( y = \sqrt{x} \), thus \( y^{2} - 3y - 4 = 0 \). Factoring gives: \( (y - 4)(y + 1) = 0 \) So, \( y = 4 \) or \( y = -1 \). Since \( y = \sqrt{x} \), only \( y = 4 \) is valid, giving \( x = 16 \). Now, let's have fun with this: Knowing what we just covered, let’s celebrate the beauty of quadratics! Did you know that the word "quadratic" comes from the Latin word "quadratus," which means "square"? It's all about those x² terms, rounding things up nicely! Quadratics aren’t just academic; they're utilized in physics, engineering, and even finance! Need to calculate projectile motion or find the best return on investment? Quadratic equations are your pals!

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy